1996
DOI: 10.1111/j.1751-0813.1996.tb13729.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of thoracic surgery in dogs and cats

Abstract: Records of 146 dogs and 41 cats that underwent thoracic surgery at The University of Sydney Veterinary Teaching Hospital were reviewed for age, sex, breed, disease, operation date, periods of pre- and post-operative hospitalisation, use of surgical drains and outcome. Animals were assigned to 16 disease categories, the most common being patent ductus arteriosus, traumatic diaphragmatic hernia and oesophageal foreign body in dogs and traumatic diaphragmatic hernia in cats. Differences were observed between dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
53
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 8 publications
15
53
1
Order By: Relevance
“…The location of hernia in this study was parallel to the several reports (1,5,8), as the majority of patients had right sided hernia. However some reports assumed that the liver has a protective effect on the right side of the diaphragm and could serve as a barrier for herniation (13).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The location of hernia in this study was parallel to the several reports (1,5,8), as the majority of patients had right sided hernia. However some reports assumed that the liver has a protective effect on the right side of the diaphragm and could serve as a barrier for herniation (13).…”
Section: Discussionsupporting
confidence: 74%
“…As in other studies (1,5,9,10,13), the most commonly reported sex was male in our study. Liver was the most frequently herniated organ and this was followed by small intestines, stomach, omentum, spleen, pancreas and large intestines (3,5,10,17).…”
Section: Discussionsupporting
confidence: 70%
“…Mainly, because we did not increase inspiratory fraction of oxygen. It is believed that those problems were secondary to the high output BPF itself, and not to other methodological factors such as surgical incision or surgical time 27 .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Bellenger et al (1996) reported survival rates of 78% for dogs and 92% for cats undergoing surgical repair of traumatic diaphragmatic hernias, whereas Schmiedt et al (2003) reported a survival rate of 82% in their study of 34 cats. The largest study to date was reported by Downs and Bjorling (1987).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only one animal died and the mortality rate was 7.69%. Diaphragmatic hernia is common in animals between 1-3 years of age (Stokhof 1986) and occurs more often in males (Stokhof 1986;Bellenger et al 1996;Schmiedt et al 2003;Hyun 2004;Minihan et al 2004). The anatomical position of the organ and the location of the disruption often determine the herniated organs in diaphragmatic hernia.…”
Section: Discussionmentioning
confidence: 99%